Analisis Kinerja Penyerapan Anggaran di Pemerintah Daerah: Studi Pemerintah Provinsi Sumatera Selatan - Alif'ia, Nabila Fitri; Hartati, Sukmini; Febriantoko, Jovan (Akuntansi & Ekonomika, 2025)
This study examines the influence of human resource quality, regional financial regulations, and understanding of financial management systems and procedures on budget absorption in the Provincial Government of South Sumatra. Using a quantitative approach, data were collected through questionnaires completed by 164 respondents from 41 regional agencies and analyzed using IBM SPSS version 26. The results show that the quality of human resources and understanding of financial systems and procedures have a significant positive effect on budget absorption. In contrast, regional financial regulations do not have a significant effect. However, collectively, the three variables have a significant simultaneous influence. These findings highlight the importance of improving competency, regulatory comprehension, and mastery of financial systems to enhance the effectiveness of budget implementation.